Hubungan Kecanduan Game Online Dengan Kesehatan Mental Pada Remaja Di Smp Negeri 4 Meulaboh - Fitri Apriani; Nurromsyah Nasution; Ratnawati Bancin; Yulfa Aulia; Muhammad Irkam (BALE LITERASI, 2025)
Background: According to the World Health Organization (WHO), it has now officially stated that online game addiction is a mental disorder. In Indonesia, there are 54.1% of adolescents aged 15-18 years who experience online game addiction, namely 77.5% of male adolescents and 22.5% of female adolescents who use time to play online games, with 2-10 hours per week. Objective: To determine the relationship between online game addiction and mental health in adolescents at SMP Negeri 4 Meulaboh. Methods: The type of research used is an analytic survey study with a cross sectional approach. This study was conducted on 58 samples selected by stratified random sampling technique and carried out from January 22 to 24, 2024. Data analysis method using Chi Square statistical test. Results: The results showed a value of 0.002 (p value